A new record Tylocephalum trygoni n.sp. (Cestoda - leacanicephalidae) from trygonzugeiat panji, Goa, India - Khamkar, D D (International Multidisciplinary Research Journal, 2011)
The present communication deals with description of new species of genus Tylocephalum trygoni n.sp. in having testes number 35-40 (38) comes closer to T. yorkei, T. elogatum, T. minutum & /. Bombayensis, however it diffres from them in shape and size of scolex, presence or absence of accessory suckers, number of testes, shape and position of ovary, shape and position of vitellaria.